Cardiovascular disease risk estimation among slums residents of Lucknow using QRISK3 calculator - Deepshikha Pandey; Shivendra K. Singh; Manish K. Manar; Abhishek Gupta (Journal of Education and Health Promotion)
INTRODUCTION: Cardiovascular diseases (CVDs) are presently the leading cause of death in India. Cardiovascular diseases are result of multiple factors. Among these risk factors, lifestyle plays a major role in the development and progression of cardiovascular diseases. Urban slum residents are disproportionately affected by CVD risk factors due to their high rates of poverty, subpar living circumstances, and limited access to social services. Early estimation of CVDs will reduce the burden on the individual, and the country. This study was conducted to estimate the risk of having a cardiovascular event (Myocardial Infarction [MI]/Stroke) after ten years by using the QRISK3 calculator. METHODS: A community-based, cross-sectional study was conducted in the slums of Lucknow, among 300 participants. The WHO 30/7 Cluster sampling technique was used to select slums. QRISK3 calculator was used to estimate 10-year CVD risk. The Chi-square test and Fisher exact test were used to analyze the data. RESULTS: The proportion of respondents with low (<10%), moderate (10-<20%), and high risk (≥ 20%) of developing CVDs after 10 years was 71.0 percent, 20.0 percent, and 9.0 percent respectively. The preponderance of developing a high risk of 10-year CVD was highly significant among the age group of 51–60 years, males, who were smokers, obese, and hypertensive participants (P < 0.01). Type 2 DM (P < 0.01), positive history of MI/angina in first-degree relatives (P = 0.02), and those who were already on anti-hypertensive medication (P < 0.01) were associated with a high (≥20%) risk of CVD after the 10-years. CONCLUSION: This study concludes that the risk of CVD events in the next 10 years is low but the risk factors associated with the CVD events (MI/STROKE) are prevalent in slum areas. Modifiable risk factors like smoking, obesity, hypertension, and Type 2 diabetes mellitus could be controlled by creating awareness among the slum population.